2015
DOI: 10.1149/2.0071508eel
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis of Gold Nanoparticles on Poly (L-arginine) Modified Glassy Carbon Electrode and Electrocatalytic Oxidation of Glucose in Alkaline Solution

Abstract: In situ synthesis of gold nanoparticles on poly (L-arginine) modified glassy carbon electrode using poly (L-arginine) as reduction agent is reported. EDAX pattern suggests that the gold nanoparticles can be in situ synthesized on poly (L-arginine) modified glassy carbon electrode. SEM image shows that the gold nanoparticles are well dispersed on the surface of glassy carbon electrode. The as-synthesized gold nanoparticles show excellent electrocatalytic activity for the oxidation of glucose. This strategy prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…5(a), in the absence of glucose, the cathodic peaks of the reverse scan at 0.16 V and 0.14 V correspond to the reduction of gold oxide produced in the forward scan. In the presence of glucose, the anodic peaks in the forward scan at −0.46 V correspond to the peaks of partial oxidation of glucose, which causes electrosorption of glucose to form adsorbed intermediate, and the anodic peak at 0.24 V represents the direct oxidation of glucose to gluconolactone5152. The reverse scan shows a strong anodic peak at 0.16 V that is formed by the direct oxidation of glucose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5(a), in the absence of glucose, the cathodic peaks of the reverse scan at 0.16 V and 0.14 V correspond to the reduction of gold oxide produced in the forward scan. In the presence of glucose, the anodic peaks in the forward scan at −0.46 V correspond to the peaks of partial oxidation of glucose, which causes electrosorption of glucose to form adsorbed intermediate, and the anodic peak at 0.24 V represents the direct oxidation of glucose to gluconolactone5152. The reverse scan shows a strong anodic peak at 0.16 V that is formed by the direct oxidation of glucose.…”
Section: Resultsmentioning
confidence: 99%
“…The reverse scan shows a strong anodic peak at 0.16 V that is formed by the direct oxidation of glucose. Because the AuOH on the gold crystal surface is the active site for electro-catalytic oxidation of glucose to take place, the population of AuOH sites is greatly enhanced in the forward scan515253; hence, direct oxidation of glucose occurs in the reverse scan. To determine the sensitivity of the dendritic Au as a glucose biosensor, the amperometric responses of the electrode were recorded with the successive addition of different concentrations of glucose at 0.3 V. By calculating the slope of the calibration of the amperometric response, the sensitivity of the dendritic electrode under certain concentration can be evaluated5455.…”
Section: Resultsmentioning
confidence: 99%
“…The EIS signals of GCE+poly­( l -arginine)+Go-AuNS composite electrodes were smaller than those EIS responses of bare GCE, l -arg, and Go-AuNS composite, which suggests a positive effectiveness of the electrochemical charge transfer rate. This may be the cause of the presence of physisorption attraction between the basal plane of the GO-AuNS composite and the l -arginine monomers with rich aromatic ring groups. , As a result, the higher number of nucleation sites were created and greatly enhanced the electropolymerization efficiency. The EIS response of the GCE+ l -arginine+Go-AuNS composite electrodes (Figure D) showed a smaller R ct value compared with that of both the poly­( l -arginine) and Go-AuNS nanocomposite (Figure B, C), proving that addition of l -arginine significantly improved the electrochemical charge transfer efficiency of the Go-AuNS nanocomposite.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers used poly amino acid to modify electrodes due to their excellent electrocatalytic properties. , For instance, poly­( l -arginine) can be spontaneously electropolymerized on the surface of electrodes for its significant outlook through the coalescence of −NH 2 and −COOH. , It was reported that poly­( l -arginine) improves the electrode response stability and the analytes electroactivity …”
Section: Introductionmentioning
confidence: 99%
“…15,16 For instance, poly(L-arginine) can be spontaneously electro- polymerized on the surface of electrodes for its significant outlook through the coalescence of −NH 2 and −COOH. 17,18 It was reported that poly(L-arginine) improves the electrode response stability and the analytes electroactivity. 16 Inorganic nanoparticles incorporated with graphene oxide (GO) were reported to lead extraordinary function for electrode modification.…”
Section: Introductionmentioning
confidence: 99%